Daily rainfall runoff modeling using artificial neural network for sungai Sarawak Kanan upper catchment - Ong, Khin Kiat. (Universiti Malaysia Sarawak (UNIMAS), 2005)
This thesis reports the results predicted from artificial neural network (ANN) models for daily rainfall-runoff simulation, at Sungai Sarawak Kanan upper catchment. The system is monitored by four rainfall gauging stations namely Kampung Monggak, Krokong, Bau and Kampung Opar located upstream of the river system and one river stage gauging station namely Buan Bidi. Backpropagation network (BP) of multilayer perceptron (MLP) is used for daily runoff simulation. Input variables used are current rainfall, antecedent rainfall and antecedent runoff while the output is current runoff. Several networks were trained and tested using data obtained from Department of Irrigation and Drainage (DID) Sarawak. The effects of different types of training algorithms, different numbers of hidden neurons, different numbers of antecedent data and different numbers of hidden layers were investigated to find the optimal neural network. Judging on coefficient of correlation R, one layered training algorithm trainoss (R = 0.839) with 150 hidden neurons and 5 days backdated performed the best for the simulations. Therefore this make this study useful for heavy rainfall predictions and thus a good tool for flood warning.